Perineální audit: důvody pro více nez 1000 epiziotomií - Rusavý, Z; Kalis, V; Landsmanová, J; Kasová, L; Karbanová, J; Dolejsová, K; Sýkora, T; Necesalová, P; Novotný, Z (Ceska gynekologie, 2011)
AIM: To analyze reasons for episiotomy use in vaginal delivery among obstetricians and midwives. Consecutively, to indentify disputable indications for its use based on published research in order to facilitate the decrease in frequency of this operation, while preserving high quality of obstetrical care. METHODS: Reasons for mediolateral episiotomy use were recorded by obstetricians and midwives after each vaginal delivery with episiotomy at the Ob&Gyn Department of the Charles University Hospital in Pilsen in the period of February 2006 - June 2007. The main reason and all reasons for episiotomy use were evaluated separately. RESULTS: The reason for episiotomy use was recorded in 1069 cases (93%) out of a total of 1150 vaginal deliveries, in which mediolateral episiotomy was performed (42% of all vaginal deliveries). The most common group of main reasons for episiotomy use was a concern about postpartum pelvic floor functional impairment (624, 58% of episiotomies), especially a rigid, non-elastic perineum (401, 37%). Fetal distress (181, 17%) and abnormalities of the expulsive forces/uncooperative parturient (109, 10%) followed. When evaluating all (including secondary) reasons, the most common groups of reasons for episiotomy use were the effort of pelvic floor functionality preservation (871, 50%), abnormalities of the expulsive forces/uncooperative parturient (354, 20%) and fetal distress (253, 15%). When evaluating episiotomies performed by obstetricians and midwives separately, the concern about postpartum pelvic floor functionality prevailed in midwives (81% vs. 39% of episiotomies performed primarily for this reason). Conversely, the obstetricians performed episiotomy more frequently for fetal distress (28% vs. 4%). CONCLUSION: In view of the fact that midwives attend only physiological deliveries in our department, the spectrum of reasons for episiotomy use among midwives is narrower and the concern about postpartum pelvic floor functionality dominates. Currently, the concern about postpartum pelvic floor functionality should not be considered a legitimate indication for episiotomy use. The fact that 624 (58%) episiotomies were performed for this reason represents a significant reserve for a decrease in the frequency of episiotomy use. The reduction should be possible primarily among midwives (81% of all main reasons for episiotomy use in the midwive group, i.e. 37% of all episiotomies performed). The analysis of reasons for episiotomy use is an important step in reduction of episiotomy rates while preserving or improving the standard of treatment provided.
Keywords: Episiotomy; epiziotomie; lidé; Female; Pelvic Floor Disorders; Pregnancy; těhotenství; onemocnění dna pánevního; ženské pohlaví; Humans